2021
DOI: 10.3389/fpsyt.2021.728990
|View full text |Cite
|
Sign up to set email alerts
|

Is Elevated Neutrophil Count and Neutrophil-to-Lymphocyte Ratio a Cause or Consequence of Schizophrenia?—A Scoping Review

Abstract: Background: Several studies have found an association between elevated neutrophil count or neutrophil-to-lymphocyte ratio (NLR) in peripheral blood from patients with schizophrenia. The etiology behind this effect is unknown, and it is unclear if changes in neutrophil count and NLR may be induced by antipsychotics or if these parameters relate to the diagnosis and symptoms of schizophrenia. The purpose of this scoping review was to map research that explores this association, and to identify gaps in the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…Increased levels of NETs were irrespective of sex, BMI, tobacco smoking, and other recreational drugs. These results extend previous findings of elevated neutrophils in schizophrenia [15][16][17][18][19][20], by mechanistically showing that these cells are in an active inflammatory state. It is becoming increasingly apparent that the release of NETs from neutrophils upon activation has a central role in both the initiation and chronicity of autoimmune and inflammatory diseases [32].…”
Section: Nets Are Elevated In the Plasma Of Early Schizophrenia Patie...supporting
confidence: 91%
See 3 more Smart Citations
“…Increased levels of NETs were irrespective of sex, BMI, tobacco smoking, and other recreational drugs. These results extend previous findings of elevated neutrophils in schizophrenia [15][16][17][18][19][20], by mechanistically showing that these cells are in an active inflammatory state. It is becoming increasingly apparent that the release of NETs from neutrophils upon activation has a central role in both the initiation and chronicity of autoimmune and inflammatory diseases [32].…”
Section: Nets Are Elevated In the Plasma Of Early Schizophrenia Patie...supporting
confidence: 91%
“…In addition, elevated NETs in our patients were not correlated with clinical variables such as duration of psychosis, psychosis age of onset, DUP, or BPRS. In two previous studies, increased blood neutrophils were associated with the severity of symptoms in FEP patients [ 16 , 80 ]. Others showed high neutrophils correlated with decreased grey matter volume and enlarged ventricles in FEP patients [ 81 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Amongst the non-affective FEP patients (schizophrenic spectrum disorder) in this cross-sectional study, we found positive correlations between symptoms severity (re ected by the PANSS factors, as well as the CGI-S) with higher NLR, but no signi cant correlations between NLR and disease onset pro le (re ected as duration of untreated psychosis (DUP)). Our study revealed no signi cant correlation between NLR and PANSS-negative symptom score, which is in parallel to ndings reported in existing review [51]. Overall it suggested the potential role of NLR as a biomarker of clinical severity in the acute episode of FEP patients.…”
Section: Discussionsupporting
confidence: 89%